1989
DOI: 10.1063/1.456676
|View full text |Cite
|
Sign up to set email alerts
|

Overtone spectroscopy of propyne and propyne-d1

Abstract: Eigenstate resolved infrared/infrared double resonance spectroscopy of the 3ν1 overtone band of 1propyne: Intramolecular vibrational energy redistribution into a Corioliscoupled bath SubDoppler, infrared laser spectroscopy of the propyne 2ν1 band: Evidence of zaxis Coriolis dominated intramolecular state mixing in the acetylenic CH stretch overtone Spectroscopy and nonradiative relaxtion of propynal J. Chem. Phys. 77, 697 (1982); 10.1063/1.443884Electronimpact spectroscopy of the alkynes: A comparison of propy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…From the above values, we predict the vibrational term value of the 2 1 ϩ 3 level at 8691.03 cm Ϫ1 , 12 cm Ϫ1 lower than the value given by Baylor et al (18). We could easily identify this band in the FTIR spectrum, as presented in Fig.…”
Section: B the 3 1 ϩ 3 Combination Bandmentioning
confidence: 88%
See 2 more Smart Citations
“…From the above values, we predict the vibrational term value of the 2 1 ϩ 3 level at 8691.03 cm Ϫ1 , 12 cm Ϫ1 lower than the value given by Baylor et al (18). We could easily identify this band in the FTIR spectrum, as presented in Fig.…”
Section: B the 3 1 ϩ 3 Combination Bandmentioning
confidence: 88%
“…The erroneous value given in Ref. (18) corresponds in fact to the maximum of the R-branch absorption. Similarly, we assigned the 1 ϩ 3 combination band, predicted at 5464.4 cm Ϫ1 to a Q-branch head observed at 5465.0 cm Ϫ1 in a highly congested region of the FTIR spectrum.…”
Section: B the 3 1 ϩ 3 Combination Bandmentioning
confidence: 94%
See 1 more Smart Citation
“…HC"CF is the molecule most affected by anharmonic resonances, but their combined effect is only 6 cm À1 on the m is (CH) frequency which may be considered as small. The overtone spectrum of propyne has also been measured up to v = 7 [56] and again, for ethynyl hydrogen, the frequency derived from Eq. (3), 3329 cm À1 is very close to the isolated frequency obtained from CD 3 C"CH, 3334 cm À1 [47].…”
Section: The Ch Bond Lengthmentioning
confidence: 99%
“…They reassigned the 4ν 1 band and showed that it is perturbed by 3ν 1 + ν 3 + ν 5 , where ν 3 and ν 5 are the C≡C and C-C stretching modes, respectively. Baylor et al (9) and Hofmann et al (10) investigated the vibrational overtone spectra of the nν 1 bands (n = 1-6) and of the nν m bands ( n = 1-7) of propyne. In addition, they studied the nν m bands (n = 1-7) and the fundamental and first overtone regions of the acetylenic C-D stretch of propyne-d 1 .…”
Section: Introductionmentioning
confidence: 99%